The meaning of the Kapiri Kame tradition and its use for education and tourism in Central Papua - Lefaan, Adolina Velomena; Yoesoef, Muhammad; Darihastining, Susi (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
The Mimika Wee tribe retains much knowledge of ancestral traditions, one of which is Kapiri Kame. This tradition is a tool and complement to the expression of life of the Mimika Wee tribe, which is inseparable from the daily life activities of the Mimika people. This research aims to describe the meaning of the Kapiri Kame tradition and its use for education and tourism in Central Papua. This research is qualitative with ethnographic methods. Sources of research data are informants, phenomena, and documents. The data collection techniques used were interviews, observation, and document study. The analysis technique used is descriptive ethnography. The research results show that the Kapire Kame tradition represents the philosophy of life of the Mimika Wee people, which is reflected in the identity of the canoe, river, and sago (3s). This symbolization emphasizes respect for fellow humans, sensitivity, and concern without intervention in other people's affairs. The various riches in this tradition can be (1) a source of local knowledge and contributor to the development of the community's economy, (2) cultural potential and creative industries that can be managed and developed to support the community's economy, (3) empowerment of community skills in processing raw materials into finished products, including the processing of forest pandan leaves into bags as women's accessories, mats for sleeping mats, as well as the use of alang-alang, melinjo and pineapple grass as traditional clothing, and (4) exploitation of natural wealth, local wisdom and art as potential culture that can be used as a cultural tourism destination industry. Based on this, the Kapiri Kame tradition is part of the philosophy of life of the Mimika Wee people, which is timeless with modernization because the values contained in it are adaptive to current developments.